2022
DOI: 10.3390/biomedicines10112983
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Linking Empagliflozin to Renal Protection in the LLC-PK1 Model of Diabetic Nephropathy

Abstract: Aims: Chronic diabetes complications, including diabetic nephropathy (DN), frequently result in end-stage renal failure. This study investigated empagliflozin (SGLT2i) effects on collagen synthesis, oxidative stress, cell survival, and protein expression in an LLC-PK1 model of DN. Methods: Combinations of high glucose (HG) and increasing empagliflozin concentrations (100 nM and 500 nM), as well as combinations of HG, H2O2, and empagliflozin, were used for cell culture treatment. The cell viability, glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Empagliflozin can reduce oxidative stress and the inflammatory response in DKD by activating the AKT/GSK3β pathway. 118 Similarly, in the comparison of improving renal insulin signaling, oxidative stress, and renal function in diabetic rats, dapagliflozin is superior to metformin with dapagliflozin downregulating GSK3β, while metformin cannot, and whether this is the reason for the difference between them has not been explained in depth by the authors. 119 Furthermore, Yi Song et al found that the hsa_circRNA_012448-hsa-miR-29b-2-5p-GSK3β pathway, which is involved in the oxidative stress response, was an important pathway mediating the action of dapagliflozin against DKD.…”
Section: Gsk3β In Predicting the Progression Of Dkdmentioning
confidence: 99%
See 1 more Smart Citation
“…Empagliflozin can reduce oxidative stress and the inflammatory response in DKD by activating the AKT/GSK3β pathway. 118 Similarly, in the comparison of improving renal insulin signaling, oxidative stress, and renal function in diabetic rats, dapagliflozin is superior to metformin with dapagliflozin downregulating GSK3β, while metformin cannot, and whether this is the reason for the difference between them has not been explained in depth by the authors. 119 Furthermore, Yi Song et al found that the hsa_circRNA_012448-hsa-miR-29b-2-5p-GSK3β pathway, which is involved in the oxidative stress response, was an important pathway mediating the action of dapagliflozin against DKD.…”
Section: Gsk3β In Predicting the Progression Of Dkdmentioning
confidence: 99%
“…Of note, evidence implies that the nephroprotective effect of these hypoglycemic drugs may be related to GSK3β. Empagliflozin can reduce oxidative stress and the inflammatory response in DKD by activating the AKT/GSK3β pathway 118 . Similarly, in the comparison of improving renal insulin signaling, oxidative stress, and renal function in diabetic rats, dapagliflozin is superior to metformin with dapagliflozin downregulating GSK3β, while metformin cannot, and whether this is the reason for the difference between them has not been explained in depth by the authors 119 .…”
Section: The Multifunction Of Gsk3β In Dkdmentioning
confidence: 99%
“…The modulation of IGF1R expression presents a potentially innovative strategy for treating DKD [ 56 ]. Furthermore, it has been observed that empagliflozin exhibits a mitigating effect on harm caused by oxidative stress through the activation of the Akt/GSK-3 signaling pathway [ 57 ] and the PPAR gamma/CD36 pathway [ 58 ]. Dapagliflozin enhances the inflammatory response in DKD by augmentation of AMPK activity and suppressing the inflammatory response mediated by the NF-κB pathway, thereby ameliorating the long-term prognosis of individuals with DKD [ 59 ].…”
Section: Research Statusmentioning
confidence: 99%